Multidimensional approach to factors affecting Japanese firms' expansion in the MENA region - Anis Khayati (Cogent Economics & Finance, 2019)
This paper investigates whether factors specific to firms, countries, mode of entry, and the timing of entry contribute to value-creation from the investment of a sample of Japanese firms in the MENA economies over the period 2006-2014. Results show that while this expansion was on average associated with positive wealth effects, such effects were relatively stronger in recent years. Also, results from firms' choice of entry mode show that the least risky modes of entry were rewarded by the highest returns. Specifically, expansion through acquisitions and new plants was on average associated with negative wealth effects compared to expansion through non-FDI modes of entry. Besides, there is an heterogeneity in wealth effects across countries. In addition, due to changing economic and institutional environments, differences in wealth effects from investments in the same country are observed overtime.
Keywords: 330; MENA region; Japanese firms; event study; entry modes; international investment